Oryza sativa cv. Nipponbare and Oryza barthii as Unexpected Tolerance and Susceptibility Sources Against Schizotetranychus oryzae (Acari: Tetranychidae) Mite Infestation - Buffon, Giseli; Blasi, Édina Aparecida dos Reis; Lamb, Thainá Inês; Adamski, Janete Mariza; Schwambach, Joséli; Ricachenevsky, Felipe Klein; Bertolazi, Amanda; Silveira, Vanildo; Lopes, Mara Cristina Barbosa; Sperotto, Raul Antonio (Frontiers in Plant Science, 2021)
Cultivated rice (Oryza sativa L.) is frequently exposed to multiple stresses, including Schizotetranychus oryzae mite infestation. Rice domestication has narrowed the genetic diversity of the species, leading to a wide susceptibility. This work aimed to analyze the response of two African rice species (Oryza barthii and O. glaberrima), weedy rice (O. sativa f. spontanea), and O. sativa cv. Nipponbare to S. oryzae infestation. Surprisingly, leaf damage, histochemistry, and chlorophyll concentration/fluorescence indicated that the African species present a higher level of leaf damage, increased accumulation of H2O2 and lower photosynthetic capacity when compared to O. sativa plants under infested conditions. Infestation decreased tiller number, except in Nipponbare, and caused the death of O. barthii and O. glaberrima plants during the reproductive stage. While infestation did not affect the weight of 1,000 grains in both O. sativa, the number of panicles per plant was affected only in f. spontanea, and the percentage of full seeds per panicle and seed length were increased only in Nipponbare. Using proteomic analysis, we identified 195 differentially abundant proteins when comparing susceptible (O. barthii) and tolerant (Nipponbare) plants under control and infested conditions. O. barthii presents a less abundant antioxidant arsenal and is unable to modulate proteins involved in general metabolism and energy production under infested condition. Nipponbare presents high abundance of detoxification-related proteins, general metabolic processes and energy production, suggesting that the primary metabolism is maintained more active compared to O. barthii under infested condition. Also, under infested conditions, Nipponbare presents higher levels of proline and a greater abundance of defense-related proteins, such as osmotin, ricin B-like lectin, and protease inhibitors. These differentially abundant proteins can be used as biotechnological tools in breeding programs aiming at increased tolerance to mite infestation.